Estimación de la susceptibilidad a deslizamientos en la Av. de los conquistadores mediante la utilización de técnicas geoespaciales - García Guamangallo, Stephany Carolina (2024)
This research focuses on estimating landslide susceptibility on Conquistadores Avenue using geospatial techniques. The study area extends from Hotel Quito to the intersection with Oswaldo Guayasamín Avenue, including indirect areas such as Cebollar, Guápulo, Jardines del Este, La Floresta, La Vicentina, Nueva Floresta, Santa Lucía, and the Monjas Protection Zone. The comprehensive susceptibility assessment was conducted by analyzing factors such as topography, vegetation cover, lithology, geomorphology, soil type, precipitation, and proximity to roads and hydrological features. By utilizing a combination of Geographic Information Systems (GIS), fuzzy logic, and multicriteria analysis, this study provides valuable insights for risk management and urban planning, emphasizing the need for a holistic approach to mitigate landslide hazards and ensure community safety and well-being.